2023
DOI: 10.53623/tasp.v3i1.131
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indoor Household Air Quality Using SentinAir's Cost-effective Sensor

Abstract: According to the World Health Organization, particulate matter (2.5 m) is responsible for more than 4 million deaths worldwide. In real-time, low-cost sensors have assisted in the measurement of PM indoors. SentiAir, a low-cost instrument used in this study, monitors particulate matter (1, 2.5, and 10), as well as nitrogen dioxide, sulphur dioxide, carbon dioxide, ozone, temperature, and relative humidity. The goal of this study was to place the sensor in a typical household indoor space and evaluate all varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…CO 2 , RH, PM 1 , PM 2.5 and PM 10 combined to create cluster 1, whereas temperature, SO 2 , NO 2 and O 3 made up cluster 2. The findings suggested that a certain cluster of contaminants may have come from anthropogenic sources (Kabir et al, 2022;Abulude, Oluwafemi, Arifalo, Elisha, & Kenni, 2023).…”
Section: Agjsrmentioning
confidence: 99%
“…CO 2 , RH, PM 1 , PM 2.5 and PM 10 combined to create cluster 1, whereas temperature, SO 2 , NO 2 and O 3 made up cluster 2. The findings suggested that a certain cluster of contaminants may have come from anthropogenic sources (Kabir et al, 2022;Abulude, Oluwafemi, Arifalo, Elisha, & Kenni, 2023).…”
Section: Agjsrmentioning
confidence: 99%